O documentário político-epistolar de Lucia Murat: uma análise de Uma longa viagem (2011) - Bianchini, Rafaella Maria Bossonello (Universidade Federal de São Carlos, 2020)
In the documentary A Long Journey (2011), by Lucia Murat, multiple layers of narrative, aesthetic, and archive collection resources (such as photographs from personal collections and excerpts from audiovisual works from external sources; testimonials; performance; verbal narration; image editing) and sounds by overlapping and alternating thematic juxtaposition, among other ways) access and crush memories in search of a rereading of the past through the epistolary narrative, hence extracting multiple and current meanings. Like the multiple layers of narrative resources, the work permeates collective and personal instances of surviving memories: the historical and social political past of the 1960s and 1970s, the generational and the personal and family. This research is intended for a narrative and aesthetic analysis of Lucia Murat's film in order to establish the concept of a contemporary political-epistolary documentary.
The political epistolary documentary by Lucia Murat: an analysis of A long journey (2011)
Keywords: Lucia Murat; Narrativa epistolar; Filme epistolar; Memória e cinema; Documentário contemporâneo; História brasileira do século XX; Epistolary narrative; Epistolary film; Memory and cinema; Contemporary documentary; Documentary and History; Brazilian History of The Twentieth Century; CIENCIAS SOCIAIS APLICADAS::COMUNICACAO